Analisis bibliometrika Islam: studi kasus dokumentasi publikasi ilmiah di UIN Syarif Hidayatullah Jakarta - Nuryudi Nuryudi (Al Maktabah, 2016)
The research on analysis bibliometrics aimed to find out the development of Islamic sciences bylooking at the productivity of the publication published in scientific journals. The research discussesthe productivity of Islamic publication at UIN Syarif Hidayatullah Jakarta in the last five years(2010 - 2014) based on e-journal bibliographic with 498 articles. The finding of the research is thefield of Shariah and Law study is the most progressive and most productive in the last five years.The indicators, more than 235 researchers contribute to the scientific publications of the period withthe accumulation of 293 articles with 4 titles published in electronic journal. Meanwhile the field ofIslamic Theology showed 107 titles of articles from 87 authors recorded on the three major journalin the same period. Others is Multi-disciplinary field registered around 98 scientific articles from75 scientists recorded on three journal titles related to the fields. In conclusion, Sharia-law is theprominent field of study in productivity and publicity of scientific Islamic publication in this period.